Protective and inappropriate antibody responses in trypanosome-infected cattle - Williams, D.J.L.; Taylor, K.; Newson, J.; Naessens, Jan; Authié, Edith (International Laboratory for Research on Animal Diseases, 1995)
The trypanosome surface coat is composed almost entirely of a homogeneous array of molecules known as variable surface glycoproteins (VSG). These molecules are highly immunogenic and elicit a strong antibody response in the infected host. Antibodies against the surface-exposed epitopes of a particular VSG mediate the destruction and clearance to trypanosomes expressing that variant. As those parasites are cleared, they are replaced by others expressing antigenically different VSG molecules, which in turn provoke specific antibody responses. Trypanosome infections are therefore characterized by waves of parasitaemia followed by waves of VSG-specific antibody. It is known that trypanotolerant N'Dama cattle infected with Trypanosoma congolense have significantly lower levels of parasitaemia than the more susceptible Boran cattle. It has been suggested that this reflects a more effective VSG-specific antibody response in the N'Damas. We have tested this hypothesis by examining VSG-specific antibody responses in N'Dama and Boran cattle during experimental infection with T. congolense.